Anatomical Structure of the Umbilical Cord in Sudanese and Correlation with Neonatal Outcome - Motaz Ahmed Abdelrahman NuggedAlla; Yasser Seddeg Abdulghani; Omer Ahmed Mirghani Osman; Haydar ElHadi Babikir (International Journal of Human Anatomy, 2021)
Background The neonatal morbidity and mortality is very high in the Sudan, the umbilical cord association and contribution to this is planned to be answered. Therefore the present study was designed to provide some information on the morphological variations of human umbilical cord via gross anatomical assessment and their correlation with foetal factors such as foetal weight and length. Methods A prospective hospital - based study conducted in Wad Madani Maternity Teaching Hospital Department of Obstetrics and Gynecology between July 2014 and March 2018 Results The mean diameter of the 371 umbilical cords was 2.1±0.24cm. Length was 53.8±3.8 cm length ranging from 48 – 62 cm and 10 (2.7%) of 371 umbilical cords were uncoiled. of which, 1 (0.3%) cords were with absent Wharton’s Jelly. The mean neonatal indices were 2.95 kg, 33.19 cm and 44.42 cm for weight, head circumference and length respectively. There was just significant strong positive correlation between umbilical cord length and length of neonates. Also Umbilical cord diameter had a positive correlation with length of neonates and negative correlation with weight of neonates and APGAR Score. Conclusion The present study suggests that ‘normal’ cord length should be between 40 cm and 70 cm in length. Umbilical cord diameter had a positive correlation with fetal length and negative correlation with fetal weight and APGAR score. The diameter range of 1-2 cm suggests that a normal cord must not exceed 2 cm in diameter. However the umbilical cord index had negative correlation with length of neonates.
Keywords: Umbilical Cord